Competences desired among educational leaders of technical education degree institutions. Issue 6 (12th August 2019) - Sharma, Payal; Pandher, Jagwinder Singh
Abstract : Purpose: This study aims to identify and classify various competences and competencies that educational leaders should essentially possess. Design/methodology/approach: The systematic review of the literature was conducted to identify various competences of educational leaders in the institutions. Later, an empirical research was conducted. The data were analyzed through confirmatory factor analysis (CFA) using AMOS 20.0 to classify these competences according to their relative importance considering natural gaps in standardized beta ( ß ) values. In all, 96 administrators of 35 technical institutions of Punjab (India) offering engineering and management programs and 93 veteran educational experts had responded in a survey. Findings: The results of the study identified five competences: pedagogical, leadership, innovative, research and evaluation competences. The competencies "help others in improvement and not blame circumstances", "set high benchmarks" and "align class activities with learning objectives" have qualified among the "most important" competencies for the educational leaders. Research limitations/implications: The sample was specific to one state. There may be the chances of response bias in a few situations. Therefore, there are few reservations in generalizing the findings. Practical implications: The study has several implications for both the faculty and the technical education degree institutes. The study provides a link between the characteristics and competencies of educational leaders. This study also contributes in terms of mapping of these competencies while recruitment of the faculty to test whether the candidates possess the potential of becoming educational leaders. Originality/value: The administrators can test these competencies in their faculty for the purpose of identifying both the educational leaders within their institutes and the potential educational leaders in future by assessing "requisite" and "important" competencies.